Analytical study of mortality in Intensive Care Unit - Reddy, R. Jayaprakash; Reddy, P. Vijaya Narasimha (International Journal of Advances in Medicine, 2019)
Background: Intensive care Unit is the one place where we come across various medical critical cases and high number of deaths is also recorded here. In spite of so many deaths occurring at this unit, cause of death is poorly reported. We studied the different causes for deaths in ICU which includes single and multiple factors for cause of death. Methods: A retrospective study performed between January 2017 to January 2018 at Rajiv Gandhi Institute of Medical sciences, Kadapa, Ongole, A.P. This study includes 260 deaths among patients admitted in ICU of our institute during this duration. We gathered data at various levels like clinical evaluation and investigations. Results: A total of 260 deaths were recorded during this study. Among these 215 (82.69%) are female and 45 (17.30%) are male. At the time of death 174 (66.92%) patients has single systemic cause 86 (33.06%) had more than one systemic cause. Cardiovascular death 50 (19.23%) is the most common cause of death among all in which CAD 28 (10.76%) are major portion and congestive cardiac failure 20 (7.6%) are the remaining portion of the cardiac deaths. Chronic kidney disease 37 (14.2%) is the next highest deaths recorded and cerebro vascular 35 (13.46%) deaths follows the next in line. Conclusions: Majority of ICU patients were present with at least one organ failure at the time of death. What we have concluded in this study is that there are more number of deaths with single systemic cause than multiple systemic causes.